Paguristes alcocki Mclaughlin & Rahayu, 2005, n. sp. - Mclaughlin, Patsy A.; Rahayu, Dwi Listyo (Zenodo, 2005)
Paguristes alcocki n. sp. (Figs 1–3) ? Paguristes ? ciliatus— Alcock 1905: 34. [Not Paguristes ciliatus (Heller, 1862)]. Paguristes ciliatus.— Gordan, 1956: 321 [in part; literature]. ? Paguristes ciliatus.— Haig & Ball, 1988: 176; Wang, 1992: 59 (list); Wang, 1994: 568; Rahayu, 2000: 392. Not Paguristes ciliatus (Heller, 1862). Paguristes ciliatus.— Wang, 1983: 50 (in part, not pl. 1: fig. 2). Not Paguristes ciliatus Heller, 1892 (see Remarks). Type material . Western Australia : holotype male (7.8 mm), 33 nautical miles N of Rosemary Island, 19°55’S, 116°36’E, 58 m, 29 Nov 1982, WAM C29554. Paratypes, 33 nautical miles N of Rosemary Island, 19°55’S, 116°36’E, 58 m, 29 Nov 1982, 2 males (6.3, 7.5 mm), WAM C16862, C16493; 39 nautical miles north of Enderby Island, 19°58.1’S, 116°27.9’E, 58–59 m, 28 Sep 1982, 1 ovig. female (5.5 mm), WAM C16751. Indonesia : Wamsoi Lagoon, Padaido, Irian Jaya, 57–91 m, 0 4 Feb 1956, 1 male (7.2 mm), RMNH. Philippine Islands : Panglao Expedition, stn L43, off Pamilacan Island, 09°30’N, 123°05’E, 60 m, 0 2 Jul 2004, 1 male (8.6 mm), NMP. Description . Thirteen pairs of quadriserial gills; branchiostegites each with few spinules on distal margin and dorsal margin distally, concealed by moderately dense setae. Shield (Figs 1 a, 3) longer than broad; dorsal surface with few tubercles or subacute spines and sparse covering of setae laterally, few scattered tufts centrally. Rostrum slender, elongate, reaching beyond bases of ocular acicles and considerably overreaching lateral projections, but broader in female, terminating acutely or with tiny spinule. Lateral projections triangular, each with tiny terminal spine. Ocular peduncles 0.7 to as long as shield length, slender, each with sparse tuft of setae basally; corneal diameter 0.1 peduncular length. Ocular acicles subtriangular, terminating acutely or in simple terminal spine; separated by less than basal width of 1 acicle. Antennular peduncles, when fully extended, not reaching to bases of corneas; basal segment with small spine ...